1998
DOI: 10.1083/jcb.142.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Human CASK/LIN-2 Binds Syndecan-2 and Protein 4.1 and Localizes to the Basolateral Membrane of Epithelial Cells

Abstract: In Caenorhabditis elegans, mutations in the lin-2 gene inactivate the LET-23 receptor tyrosine kinase/Ras/MAP kinase pathway required for vulval cell differentiation. One function of LIN-2 is to localize LET-23 to the basal membrane domain of vulval precursor cells. LIN-2 belongs to the membrane-associated guanylate kinase family of proteins. We have cloned and characterized the human homolog of LIN-2, termed hCASK, and Northern and Western blot analyses reveal that it is ubiquitously expressed. Indirect immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
303
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(315 citation statements)
references
References 55 publications
8
303
1
3
Order By: Relevance
“…Our results suggest that DLG-1 might function in a previously unknown mechanism (in addition to that of cadherins and catenins) by which actin filaments are attached to and regulated by adherens junctions during the morphological movements of cells. Indeed, other MAGUK proteins have been shown to bind to actin/spectrin-binding protein 4.1 family members or complex with cortactin through GKAP and Shank (Cohen et al, 1998;Jons et al, 1999;Marfatia et al, 1994;Marfatia et al, 1996;Naisbitt et al, 1999). Our results show that a MAGUK protein, DLG-1, is required for the proper organization of the actin cytoskeleton, and raise the possibility that the binding observed between MAGUK proteins and actin-binding proteins is important for cytoskeletal organization in other systems.…”
Section: Discussionmentioning
confidence: 53%
“…Our results suggest that DLG-1 might function in a previously unknown mechanism (in addition to that of cadherins and catenins) by which actin filaments are attached to and regulated by adherens junctions during the morphological movements of cells. Indeed, other MAGUK proteins have been shown to bind to actin/spectrin-binding protein 4.1 family members or complex with cortactin through GKAP and Shank (Cohen et al, 1998;Jons et al, 1999;Marfatia et al, 1994;Marfatia et al, 1996;Naisbitt et al, 1999). Our results show that a MAGUK protein, DLG-1, is required for the proper organization of the actin cytoskeleton, and raise the possibility that the binding observed between MAGUK proteins and actin-binding proteins is important for cytoskeletal organization in other systems.…”
Section: Discussionmentioning
confidence: 53%
“…We therefore conclude that the absence of the intracellular domain of either syndecan has a dominantnegative effect on bacterial uptake, probably by preventing a necessary tight interaction of the endogenous syndecans with signalling molecules or the cytoskeleton. It has been shown that the last four amino acids of the intracellular domain of all syndecans are strictly conserved (amino acids EFYA) and are responsible for mediating interaction with several proteins containing PDZ domains (Grootjans et al, 1997;Cohen et al, 1998;Hsueh et al, 1998). One of these proteins, CASK, binds to protein 4.1, thereby connecting the complex to the actin cytoskeleton .…”
Section: Discussionmentioning
confidence: 99%
“…46 CD2AP binds actin 47 and has been suggested to link nephrin to the actin cytoskeleton. 39 CASK may also participate in linking nephrin to actin, as CASK has previously been shown to connect other membrane proteins, eg, syndecan-2 44 and neurexins, 48 to the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…23 CASK has been shown to be present in many epithelial cells including MDCK cells. [42][43][44] We performed immunoblotting with CASK antibodies on glomerular proteins that bound to GST-nephrin tail and confirmed the presence of CASK ( Figure 9B). We also performed pull-down assays with GST-CD2AP on glomerular lysates and found that CASK binds to GST-CD2AP but not to GST alone ( Figure 9C).…”
Section: Nephrin Associates With Cask In Glomerulimentioning
confidence: 99%